2005
DOI: 10.1590/s1413-70542005000600004
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de embriões imaturos de citros em diferentes concentrações de carvão ativado e ácido giberélico

Abstract: RESUMOAdição de carvão ativado e giberelina no meio de cultura podem proporcionar melhores condições no desenvolvimento de embriões imaturos de citros. Objetivou-se avaliar o efeito de carvão ativado e GA 3 (ácido giberélico) no cultivo de embriões imaturos provenientes do cruzamento entre laranjeira Pêra Rio x tangerineira Poncã . Após 118 dias da polinização, frutos imaturos, com 3 a 4 cm de diâmetro, foram coletados, suas sementes removidas e tratadas com álcool (70%) por cinco minutos, hipoclorito de sódio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
7
0
6
Order By: Relevance
“…Given the efficiency of activated carbon to adsorb undesirable compounds, which are occasionally present in the medium, it follows that it also acts on the desirable substances, making them unavailable for the explant, indicating there is a tolerable limit for this agent to the culture medium. The optimal dose in this study was approximately 2,5 g L -1 , a result that corroborates those found by Chagas et al (2005) and Schneiders et al (2012) who worked with Cattleya harrisoniana and several species of citrus, respectively. An adequate supply of activated charcoal is an essential requirement for the satisfactory performance of explants in vitro.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Given the efficiency of activated carbon to adsorb undesirable compounds, which are occasionally present in the medium, it follows that it also acts on the desirable substances, making them unavailable for the explant, indicating there is a tolerable limit for this agent to the culture medium. The optimal dose in this study was approximately 2,5 g L -1 , a result that corroborates those found by Chagas et al (2005) and Schneiders et al (2012) who worked with Cattleya harrisoniana and several species of citrus, respectively. An adequate supply of activated charcoal is an essential requirement for the satisfactory performance of explants in vitro.…”
Section: Resultssupporting
confidence: 90%
“…Several authors have concluded that despite the beneficial effect of activated charcoal, including the absorption of toxic components and medium impurities, it also acts on the useful agents, such as sucrose, salts, and in some cases growth regulators, making them inactive or unavailable for the explant. Thus, they suggest that concentrations between 0.1% and 2.0% are within the desirable range for the safe application of this component (BOULAY, 1964;CHAGAS et al, 2005;GRATTAPAGLIA;MACHADO, 1998;RICCI et al, 2002). Means followed by the same capital letter in a column do not differ by Tukey test at 5% probability; CV: coefficient of variation; LSD: least significant difference.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The often-inhibitory effect on growth, observed for treatments with activated charcoal, may be due to the adsorbent property of activated charcoal so that acting as both growth promoter and inhibitor. This is attributed to an excellent pore network with a great internal surface of the activated charcoal, wherein several culture-medium inhibitory substances or toxic products released by explants can remain adsorbed (CHAGAS et al, 2005;THOMAS, 2008). As a result, this compound adsorbs not only toxic compounds but also essential nutrients to plant growth, which are released slowly (GUSON; MORAES; RONCONI, 2012; VILLA; PASQUAL; SILVA, 2014).…”
Section: Figure 1 Protocorms Of Oeceoclades Maculata (Lindl) With Lmentioning
confidence: 99%
“…The use of activated charcoal in the culture medium, a form of carbon with a high surface area, is known to present elevated capacity to adsorb numerous toxic compounds during in vitro cultivation (Nunes et al, 2008), such as phenolic exudates and excess ethylene produced inside the culture jars (Ribeiro et al, 2000;Chagas et al, 2005;Thomas, 2008).…”
Section: Introductionmentioning
confidence: 99%